Assessing e-learning system in higher education institutes: Evidence from structural equation modelling - Muhammad, Ali; Syed Ali, Raza; Wasim, Qazi; Puah, Chin Hong (Emerald Group Publishing Ltd., 2018)
Purpose: This study aims to examine university students’ acceptance of e-learning systems in Pakistan. A Web-based learning system is a new form of utilizing technological features. Although, developed countries have initiated and established the concept for e-learning, developing countries require empirical support to implement e-learning. Design/methodology/approach: This paper further explains a conceptual model that is based on the technology acceptance model (TAM). Earlier theories such as the theory of reasoned action (TRA), theory of planned behaviour (TPB) and decomposed theory of planned behaviour (DTPB) have been conducted on user behavioural intention (BI). TAM is considered as the most relevant framework in a Web-based context. To analyse the present study’s hypothesized model, structural equation modelling (SEM) has been used to statistically analyse self-reported sample data from 424 university students. Findings: The results revealed that TAM, with the combination of new constructs, explains university students’ acceptance of the e-learning system reasonably well. Additionally, work life quality (WLQ) and facilitating conditions (FC) have a greater influence on the BI and the actual use (AU) of the e-learning system, respectively. Originality/value: The study has also provided valuable implications for academics and practitioners for ways to enhance the acceptance of the e-learning system in the higher education of Pakistan. © 2018, Emerald Publishing Limited.